The development of women magazines in Malaysia and its educational impact on Muslim women - Mohamed, Shafizan (IIUM Press, 2009)
The first women magazine in Malaysia was published in 1932 to a limited audience. The development of the women magazines was slow until the surge of demand for the magazine's genre occurred in the 1960s and I970s. Today, there are more than 50 local magazines that are specifically focused on local women. In this chapter, the development of women magazines in Malaysia will be analyzed in the context of Malay magazines that mostly target Muslim women in Malaysia. To delineate this development, this chapter is divided into 4 major topics, namely, historical development of women magazines in Malaysia; Islamic-based women magazines in Malaysia; current state of women magazines in Malaysia and evaluation of the role of these magazines in educating Muslim readers.